PROFIL KINERJA PENGAWAS MADRASAH KEMENTERIAN AGAMA LAMPUNG SELATAN - Rosidah Rosidah; Supomo Kandar; Irawan Suntoro (9 772338317006)
The purpose of this study is to describe and analyze regarding: 1) academic and managerial supervision, 2) guide and train professional teachers, 3) implementation of professional development supervisor, 4) factors supporting and inhibiting factors supervisor performance and, 5) the efforts of the agencies in improving the performance of madrassas supervisors. This type of research is qualitative and phenomenological approach as a case study research design. Results of the study: 1) academic and managerial oversight begins with planning but in the implementation and in reporting the results of supervision is not optimal; 2) guide and train professional teachers through KKG / MGMPs; 3) the implementation of professional development supervisor has not been seen; 4) the performance of the supporting factors were little. (5) the efforts of the regulatory agencies in improving the performance as well as the recruitment of candidates for superintendent is doing well.Tujuan dari penelitian ini adalah untuk mendeskripsikan dan menganalisis mengenai: 1) akademik dan manajerial pengawasan, 2) panduan dan melatih guru-guru profesional, 3) pelaksanaan pengawas pengembangan profesional, 4) faktor pendukung dan penghambat kinerja faktor pengawas dan, 5) upaya lembaga dalam meningkatkan kinerja pengawas madrasah. Jenis penelitian ini adalah pendekatan kualitatif dan fenomenologis sebagai desain penelitian studi kasus. Hasil penelitian: 1) pengawasan akademik dan manajerial dimulai dengan perencanaan, tetapi dalam pelaksanaannya dan melaporkan hasil pengawasan tidak optimal; 2) panduan dan melatih guru-guru profesional melalui KKG / MGMP; 3) pelaksanaan pengawas pengembangan profesional belum terlihat; 4) kinerja faktor pendukung masih kecil; 5) upaya badan hukum dalam meningkatkan kinerja serta perekrutan calon pengawas berjalan dengan baik.Kata kunci: profil, kinerja, pengawas madrasah, kementerian agama